PENGARUH PEMANGKU KEPENTINGAN DALAM MENINGKATKAN KINERJA USAHA INDUSTRI BORDIR DI PROVINSI ACEH - YULI KUSDIARNI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
A role synergy between stakeholders in creation of access and mobilization of entrepreneurs greatly influences their business’s performance. The author is, in this research, interested to observe stakeholders’ role which leads to higher success in embroidery industry. This research aims at testing the influence of stakeholders, –government, academics, entrepreneurs, association and financial institution–, on the improvement of embroidery industry’s business performance in Aceh. This research takes 200 entrepreneurs as its samples and tests the hypotheses by employing the multiple linear regression analysis. The analysis results conclude that government and entrepreneurs significantly influence the improvement of embroidery industry’s business performance. However, academics, association and financial institution do not significantly influence the improvement of embroidery industry’s business performance.